Investigating the CCAAT/Enhancer-Binding Protein Beta-Regulated Tumour-Derived Secretome in Cancer Cachexia - Syed, Ayesha (Université d'Ottawa / University of Ottawa, 2025)
Cancer cachexia is a paraneoplastic syndrome characterized by muscle wasting, often driven by cachexia-inducing factors (CIFs). This thesis investigates the role of CCAAT/enhancer-binding protein β (C/EBPβ) in regulating the cancer secretome responsible for inducing cachexia. Using murine cancer cell lines, the study assessed the atrophic potential of conditioned media, extracellular vesicles (EVs), and apoptotic bodies, linking their effects to C/EBPβ expression. A TurboID-based enzymatic biotinylation system was developed to tag and isolate secreted proteins for proteomic profiling. Mass spectrometry revealed 24 unique secreted proteins, many associated with vesicular transport, whose expression was modulated by C/EBPβ. RNA-sequencing analysis confirmed that C/EBPβ knockout altered secretome composition more significantly than overexpression. These findings support C/EBPβ as a key regulator of cachexia-inducing factors and validate TurboID as a powerful tool for in vitro secretome profiling. This work advances our understanding of tumor-host communication in cachexia and identifies potential targets for therapeutic intervention.
Keywords: Cancer cachexia; C/EBPβ; TurboID; Secretome; Extracellular vesicles; Proteomics